PENANAMAN ETIKA DIGITAL MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS 5 SD - Amellia Febriana, Dhea; Sukron Djazilan , M.; Widiana Rahayu, Dewi; Mariati, Pance (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Pancasila Education in instilling digital ethics in fifth-grade students at SDN X Surabaya. This research is motivated by the increasing use of digital technology among elementary school students, which influences their attitudes and behaviors in using digital media. The research method used was descriptive qualitative. Data collection was conducted through observation, interviews, and documentation, involving teachers and students as data sources.The results indicate that the implementation of Pancasila Education in instilling digital ethics is carried out through teacher role models, habituation activities, the integration of Pancasila values into the learning process, and the use of contextual learning media appropriate to students' daily lives. Teachers play a crucial role in providing guidance and examples to students regarding the wise and responsible use of digital media. Based on the research results, some students have implemented digital ethics in their daily lives, such as using polite language when communicating on digital media, respecting the opinions of others, and using digital media responsibly. However, this study also identified several obstacles, such as a lack of supervision of students' digital media use outside of school and differences in students' understanding of digital ethics. Therefore, collaboration between teachers, schools, and parents is necessary to strengthen the sustainable instilling of digital ethics in students. This study concludes that Pancasila Education plays a crucial role in shaping elementary school students' digital ethics in the digital era and supports the development of more responsible, disciplined, and wise character in their daily use of digital technology.